Silent circulation of St. Louis encephalitis virus prior to an encephalitis outbreak in Cordoba, Argentina (2005). - Luis Adrian Díaz; Guillermo Albrieu Llinás; Ana Vázquez; Antonio Tenorio; Marta Silvia Contigiani (Public Library of Science (PLoS), 2012)
St. Louis encephalitis virus is a complex zoonoses. In 2005, 47 laboratory-confirmed and probable clinical cases of SLEV infection were reported in Córdoba, Argentina. Although the causes of 2005 outbreak remain unknown, they might be related not only to virological factors, but also to ecological and environmental conditions. We hypothesized that one of the factors for SLE reemergence in Córdoba, Argentina, was the introduction of a new SLEV genotype (SLEV genotype III), with no previous activity in the area. In order to evaluate this hypothesis we carried out a molecular characterization of SLEV detections from mosquitoes collected between 2001 and 2004 in Córdoba city. A total of 315 mosquito pools (11,002 individuals) including 12 mosquitoes species were analyzed. Overall, 20 pools (8 mosquitoes species) were positive for SLEV. During this study, genotypes II, V and VII were detected. No mosquito pool infected with genotype III was detected before the 2005 outbreak. Genotype V was found every year and in the 8 sampled sites. Genotypes II and VII showed limited temporal and spatial activities. We cannot dismiss the association of genotype II and V as etiological agents during the outbreak. However, the silent circulation of other SLEV strains in Córdoba city before the 2005 outbreak suggests that the introduction of genotype III was an important factor associated to this event. Not mutually exclusive, other factors such as changes in avian hosts and mosquitoes vectors communities, driven by climatic and environmental modifications, should also be taken into consideration in further studies.